(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s ((3TgGH GdOjf CMeO Hf CHj GdaVd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd dcd OGA OhGA aEf GdYde HGdCOhjI GdeaQOI hbhGgG dGjSJZfi GdWHjH Yfg hbO LeYJ ai gPG GdcJGH ef gPg GdCfhGY eG GfJgi Edni Ydeg s
(3BNQgG (B:s
(3TQH GdeGA jVQ HGdeYOI hjHQOgG Je hGddg SHMGfg hJYGdi CYde s
(3GfXQ agQS GdWH HQbe (B70 (3GdLGeY aj GdCOhjI GdeaQOIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B74 s
Keywords: (3GdWHs